VT-1598 Inhibits the in vitro Growth of Mucosal Candida Isolates and Protects Against Oropharyngeal Candidiasis in IL-17 Deficient Mice - Break, Timothy J (Open Forum Infect Dis, 2017)
BACKGROUND: Patients with chronic mucocutaneous candidiasis (CMC) often develop azole-resistant Candida infections, making treatment difficult due to lack of oral antifungal drug options. VT-1598 is a novel broad-spectrum fungal CYP51 inhibitor designed for exquisite selectivity for the fungal target versus human CYP enzymes to circumvent classic azole side effects like drug–drug interactions. We report the efficacy of VT-1598 in the treatment of oral Candida infection (including by azole-resistant strains). METHODS: The in vitro MIC values of 28 Candida species isolated from patients with CMC due to AIRE mutations were tested against VT-1598 and fluconazole (FLC), using CLSI broth microdilution M27-S4. Plasma VT-1598 levels were measured using LC–MS/MS with electrospray ionization. Tongue fungal load was determined in IL-17 deficient Act1(- /-) mice following sublingual C. albicans infection and once-daily oral treatment for 4 days with 25 mg/kg FLC or 3.2, 8, and 20 mg/kg VT-1598 starting 18 hours post-infection. RESULTS: Among 28 Candida isolates tested (22 C. albicans, three C. glabrata, and one each of C. utilis, C. dubiliensis, and C. krusei), 10 (36%) were not susceptible to FLC, based on CLSI breakpoints (>4 mg/ml). Remarkably, all 28 isolates were highly susceptible to VT-1598 (MIC(50) and MIC(90), 0.06 and 0.125 mg/ml, respectively). Oral administration of VT-1598 led to mean drug levels in mouse plasma (2.0, 3.0, and 11 mg/ml at the low, mid, and high doses, respectively) that were higher than the MIC values. In vivo, VT-1598 was significantly more effective, compared with FLC, against FLC-susceptible and -resistant C. albicans, and led to elimination of fungal growth even at the lowest tested dose (3.2 mg/kg). After a 10-day washout period from the last dose, mice treated with VT-1598 did not have mucosal fungal growth, while mice treated with FLC had tongue fungal loads similar to vehicle control. CONCLUSION: VT-1598 shows in vitro activity against mucosally derived Candida, including FLC-resistant strains. In vivo, VT-1598 achieves high plasma concentrations and eliminates viable C. albicans, even at low doses and after an extended washout period. These data indicate that VT-1598 may be a significantly improved treatment option for patients with CMC. DISCLOSURES: C. M. Yates, Viamet Pharmaceuticals, Inc.: Employee, Salary. O. J. Cohen, Viamet Pharmaceuticals, Inc.: Employee, Salary. R. J. Schotzinger, Viamet Pharmaceuticals, Inc.: Employee, Salary. E. P. Garvey, Viamet Pharmaceuticals, Inc.: Employee, Salary. M. Lionakis, Viamet Pharmaceuticals: Research support (CRADA), Research support